Advantages and Disadvantages of Down-the-Hole Hammer Blasthole Drilling vs. Rotary Drilling in Large Scale Open Pit Surface Mining - George D. Raitt; Rudy Lyon (International Society of Explosives Engineers, 1998)
Until fairly recently, Down-The-Hole (DTH or DHD) hammer drilling was never really a factor in large scale open pit surface mining. It was a method confined to water well drillers, aggregate quarries and limestone mines where the hole size rarely exceeded 6-1/2" (165 mm). Also it was somewhat limited to the harder rock areas such as the North East and South East United States. The trend in the big mining pits for coal, copper, gold and iron, was for the big rotary drill rigs with lots of muscle in pulldown, bitload and rotary torque.